(untitled) - Islam, Iyanatul (London, 1997)
Contents: Pt. I. Asia-Pacific economic development: selected issues and themes. 1. The emergence of an integrated Asia-Pacific economy. 2. Public policy and political economy. 3. Macroeconomic stabilisation and economic performance. 4. The financial system and economic development. 5. Labour market institutions, human resources and economic performance. 6. Managing the environment in rapidly industrialising economies. 7. Poverty, inequality and economic development. 8. Epilogue: Democracy and development in the Asia-Pacific region
Keywords: Đông Nam Á,Southeast Asia; Chính sách kinh tế,Economic policy